Odpowiedź :
Odpowiedź:
[tex]4sin^3x +sin2x = 2sin^2x (2cosx+1)\\[/tex]
Zamieniamy ze wzoru: [tex]sin2\alpha = 2sin\alpha cos\alpha[/tex]
[tex]4sin^3x +2sinxcosx = 2sin^2x (2cosx+1)|:2\\2sin^3x +sinxcosx =sin^2x(2cosx+1)\\2sin^3x +sinxcosx =2sin^2xcosx +sin^2x \\2sin^3x -sin^2x +sinxcosx - 2sin^2xcosx = 0 \\sin^2x (2sinx-1) -sinxcosx(2sinx -1) = 0 \\(2sinx-1)(sin^2x -sinxcosx) = 0\\[/tex]
Przyrównujemy każdy iloczyn do zera
[tex]2sinx -1 = 0\\sinx = \frac{1}{2} \\sinx = sin\frac{\pi }{6} \\\\x = \frac{\pi}{6} + 2k\pi\\\\x = \frac{5\pi}{6} + 2k\pi\\[/tex]
lub
[tex]sin^2x -sinxcosx = 0 \\sinx(sinx-cosx) = 0\\sinx = 0 \\x = k\pi\\sinx - cosx = 0 \\sinx = cosx |:cosx\\\frac{sinx}{cosx} =1\\tgx = 1\\x = \frac{\pi}{4} + k\pi\\[/tex]
Otrzymaliśmy więc 4 serie rozwiązań. Pozdrawiam:)